Physiotherapy intervention for posture improvement in individual with scoliosis: A case study - Adnan Faris Naufal; Arif Setiawan; Pramudya Kurnia; Anida Azkia Fitri (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Scoliosis is a structural spinal deformity marked by an abnormal sideways curvature and a loss of the spine's natural front-to-back alignment, resulting in postural imbalances. This study investigates how physiotherapy interventions improve posture in individuals with scoliosis. Methods: This qualitative descriptive-analytic case study utilized physiotherapy interventions such as stretching exercises, Pilates, core stability training, myofascial release, and manipulation therapy. Outcome measures included a scoliometer (spinal curvature), goniometer (lumbar range of motion), McGill's Torso Muscular Endurance Test Battery (core endurance), volumetric exerciser (lung capacity), measuring tape (limb length), Clarke's angle method (foot arch assessment), and Zebris FDM (body force pressure and center of pressure movement during stance). Results: Physiotherapy improved postural alignment, reducing spinal curvature from 9 degrees to 3 degrees and increasing lumbar flexion from 61 degrees to 75 degrees. Core endurance increased, as evidenced by a 1.06-second improvement in the flexion-extension ratio and a 0.90-second bilateral increase in side-bridge endurance. Limb length discrepancy decreased from 2.5 cm to 0.5 cm, enhancing symmetry in both true and apparent lengths. Foot arch asymmetry also improved, with the right arch increasing from 45 degrees to 46 degrees and the left from 39.7 degrees to 42.5 degrees. Conversely, lung capacity declined from 1363 mL to 1238 mL. Force pressure distribution became more asymmetrical in most cases, particularly affecting the longer limb in individuals with scoliosis, and center of pressure movement increased from 51.5 mm to 76.5 mm, indicating altered balance and postural control. Conclusion: Over two months, physiotherapy effectively improved postural alignment and musculoskeletal function in individuals with scoliosis.